Lost souls meet under a full moon - Tsujimura, Mizuki, 1980- (Scribner, An Imprint of Simon & Schuster, LLC, 2025)
"I bring together the living and the departed. I am the go-between. When a young woman from Tokyo contacts the go-between to request a meeting with a deceased TV star who once helped her, she doesn't expect a teenage boy to show up. Dressed in a designer duffel coat and carrying a tattered notebook, Ayumi Shibuya offers an extraordinary service: he reunites the living with their dearly departed. Meeting his clients at a luxury hotel, Ayumi lays down the ground rules: each reunion is a one-time arrangement that the dead can refuse, the service is entirely free, and the meeting must take place during a full moon. As Ayumi arranges these reunions, we encounter a resentful eldest son who wants to ask his mother to unearth the deeds to a plot of land, a teenage girl who blames herself for her best friend's death, and a weary businessman seeking answers about his fiancée's disappearance days after he proposed."--